2013
DOI: 10.1124/dmd.113.053777
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Metabolism of Benzo[a]pyrene in Rainbow Trout (Oncorhynchus mykiss): A Comparison between the Liver and Immune Organs

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are immunotoxicants in fish. In mammals, phase I metabolites are believed to be critically involved in the immunotoxicity of PAHs. This mechanism has been suggested for fish as well. The present study investigates the capacity of immune organs (head kidney, spleen) of rainbow trout, Oncorhynchus mykiss, to metabolize the prototypic PAH, benzo [a]pyrene (BaP). To this end, we analyzed 1) the induction of enzymatic capacity measured as 7-ethoxyresorufin-O-deethylase (EROD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…This alteration in gene expression was followed by alterations in the respective metabolic enzyme capacities. In BaP-exposed O. mykiss, changes in the expression of CYP1A were paralleled by the formation of BaP metabolites and therefore are suggested to mirror the response of the xenobiotic metabolism in this species [37]. Accordingly, our findings on the increased expression of both AhR and CYP1A, which remains elevated at least 10 d after injecting BaP, reflect that it might take a longer time to biotransform xenobiotics in Antarctic eelpout compared with temperate species.…”
Section: Effects Of Bap On Cyp1a Expressionmentioning
confidence: 52%
See 2 more Smart Citations
“…This alteration in gene expression was followed by alterations in the respective metabolic enzyme capacities. In BaP-exposed O. mykiss, changes in the expression of CYP1A were paralleled by the formation of BaP metabolites and therefore are suggested to mirror the response of the xenobiotic metabolism in this species [37]. Accordingly, our findings on the increased expression of both AhR and CYP1A, which remains elevated at least 10 d after injecting BaP, reflect that it might take a longer time to biotransform xenobiotics in Antarctic eelpout compared with temperate species.…”
Section: Effects Of Bap On Cyp1a Expressionmentioning
confidence: 52%
“…This alteration in gene expression was followed by alterations in the respective metabolic enzyme capacities. In BaP‐exposed O. mykiss , changes in the expression of CYP1A were paralleled by the formation of BaP metabolites and therefore are suggested to mirror the response of the xenobiotic metabolism in this species .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moller et al . ). Studies on dietary PAH exposures are limited, especially concerning PAH and vitamin effects in the intestine, which is the first barrier for dietary PAH exposure, vitamin uptake and vitamin conversion.…”
Section: Metabolizationmentioning
confidence: 97%
“…PAHs and phenols have been shown to suppress non-specific cytotoxic cells in teleosts, which are relevant in the immunologic defense from xenogenic targets, like certain fish parasites (Faisal et al, 1991;Graves et al, 1985;Reynaud and Deschaux, 2006;Seeley and Weeks-Perkins, 1997;Taysse et al, 1998). Beyond, Möller et al (2014) demonstrated that PAHs are distributed into the immune organs head kidney and spleen in fish, and that those possess the capability to metabolize PAHs to potentially immunotoxic metabolites, which in their turn may diminish immunological responses (Khan and Thulin, 1991). Further, an increased pollution of the water with organic material can cause an increased reproduction of macroinvertebrates that can serve as intermediate hosts.…”
Section: Histopathological Evaluation Of P Vachelliimentioning
confidence: 98%